2012
DOI: 10.1007/s10534-012-9551-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hydrogen sulfide and nitric oxide in the alleviation of cadmium-induced oxidative damage in alfalfa seedling roots

Abstract: Despite hydrogen sulfide (H(2)S) and nitric oxide (NO) are important endogenous signals or bioregulators involved in many vital aspects of plant growth and responses against abiotic stresses, little information was known about their interaction. In the present study, we evaluated the effects of H(2)S and NO on alfalfa (Medicago sativa L.) plants exposed to cadmium (Cd) stress. Pretreatment with an H(2)S donor sodium hydrosulfide (NaHS) and well-known NO donor sodium nitroprusside (SNP) decreased the Cd toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(105 citation statements)
references
References 60 publications
9
95
1
Order By: Relevance
“…Recent studies in plants revealed that H 2 S plays multiple roles in the modulation of various physiological processes [3], such as copper, cadmium, drought, salinity and heat et al [6][7][8][9][10]. In addition, our results indicate that the content of H 2 S was rapidly increased by low temperature.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Recent studies in plants revealed that H 2 S plays multiple roles in the modulation of various physiological processes [3], such as copper, cadmium, drought, salinity and heat et al [6][7][8][9][10]. In addition, our results indicate that the content of H 2 S was rapidly increased by low temperature.…”
Section: Discussionsupporting
confidence: 56%
“…Many data indicate that most of the endogenously synthesized H 2 S occurred via L-cysteine desulfhydrase (LCD, EC4.4.1.1) and D-cysteine desulfhydrase (DCD, EC4.4.1.15) in high plants [2][3][4][5]. Recent studies show that H 2 S is involved not only in plant responses to drought and copper stresses but also in tolerance to salinity, heat, cadmium, boron and chromium stresses [6][7][8][9][10]. It is reported that exogenous H 2 S can enhance the resistance of plants to drought stress [11][12][13][14] and copper stress [15,16] by improving the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD).…”
Section: Introductionmentioning
confidence: 99%
“…As for animal systems, in plants, there is controversial evidence about H 2 S-NO interaction. On one hand, it was shown that H 2 S acts upstream of NO in root organogenesis and heavy metal toxicity (Zhang et al, 2009a;Li et al, 2012). On the other hand, H 2 S was reported to act downstream of NO in the ethylene-induced stomatal closure and in the resistance to heat stress (Liu et al, 2012;Li et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of hydrogen sulfide metabolism have important pathological consequences, establishing the clinical relevance of this molecule (Ɓowicka and BeƂtowski, 2007;SzabĂł, 2007;Wang, 2012). In addition to the protective effects of hydrogen sulfide against a wide array of different stresses that have been demonstrated in plants (Zhang et al, 2008Wang et al, 2010;Jin et al, 2011;Dawood et al, 2012;Li et al, 2012aLi et al, , 2012bCheng et al, 2013;Christou et al, 2013;Sun et al, 2013), this molecule has also been shown to regulate plant processes that are critical for plant performance, such as photosynthesis (Chen et al, 2011), stomatal movement (GarcĂ­a-Mata and Lamattina, 2010;Lisjak et al, 2010;Scuffi et al, 2014), and autophagy (Álvarez et al, 2012b; Gotor et al, 2013). In this study, we provide new experimental evidence that, together with our previous findings, demonstrates the role of hydrogen sulfide in regulating the progression of autophagy independently of the condition in which the autophagy originates.…”
Section: Discussionmentioning
confidence: 99%